The timber industry in Peru - Carrión M., Rolando (2002)
It is part of the proven fact that Peru's natural resources: forests, marine, mining, etc.. exported without value added. The University fulfill its role in society, should make proposals to give greater value to the various natural resources of the country before being exported. Industrialization is a way to get it; industrialization but to be effective it must be based on research.